The Relationship of Self-Efficacy Between Resilience and Life Quality of Caregivers Toward Schizophrenics - Nihayati, Hanik Endang; Isyuniarsasi, Ira; Tristiana, Rr. Dian (International Journal of Psychosocial Rehabilitation, 2020)
Taking over the responsibility of caring for schizophrenics without training and limited resources causes a lack of confidence in caregivers. Physical activity, emotional, social pressure felt continuous, and these will have impacts on resilience and life quality of caregivers. This study aimed to reveal the relationship of self-efficacy between resilience and life quality of schizophrenic caregivers. Cross-sectional with quantitative data of 216 schizophrenia caregivers who visited the mental clinic. This sample was taken based on a purposive sampling technique. The instruments used were Generally Self-Efficacy Scale (GSES) Questionnaire, Connor-Davidson Resilience Scale (CD-RISC) Questionnaire, and Schizophrenia Caregiver Quality of Life Questionnaire (SC-QoL) questionnaire, and then these instruments were analyzed by Spearman Rho statistical correlation test. In this study, the first variable shows a significant relationship between self- efficacy toward resilience in schizophrenic caregivers with p-value = 0,000 and r = 0.435. It indicates the higher the self-efficacy of caregivers, the higher the resilience. In the second variable, there is a significant but inversely related to self-efficacy and the life quality of schizophrenic caregivers. It can be seen from the p-value= 0.039 with r = -0.141. It indicates the higher the self-efficacy of caregivers, the worse the quality of life.